Thrombotic complications of vaccination against SARS-CoV-2: what pharmacovigilance reports tell us – and what they don't. Issue 1 (1st July 2021) - Konstantinides, Stavros V.
In the present issue of the European Respiratory Journal, Smadja et al. [1] present an analysis of global pharmacovigilance reports of thrombotic events following severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2) vaccination. More specifically, the authors analysed the data entered into the World Health Organization (WHO) Global Database for Individual Case Safety Reports (VigiBase) between 13 December, 2020 and 16 March, 2021, covering, at that time, a population of almost 362 million vaccinated individuals across the world. The study focuses on three of the coronavirus disease 2019 (COVID-19) vaccines available to date, namely Pfizer-BioNtech (BNT162b2), Moderna (mRNA-1273) and OxfordAstraZeneca (ChAdOx1 nCov-19). The study by Smadja et al. [1] confirms the rarity of possible thrombotic complications in association with COVID-19 vaccination, reporting only 0.21 (95% CI 0.19–0.22) cases of thrombotic events per million person vaccinated-days. However, there were also some unexpected observations which deserve closer attention and cautious interpretation. Thrombotic complications of COVID-19 vaccination are very rare, but awareness is needed https://bit.ly/3n4vaXe